X-ray Characterization of Nanostructured Energy Materials by Synchrotron Radiation - Luca Petaccia; Mehdi Khodaei (IntechOpen, 2017)
Nowadays, nanomaterials are attracting huge attentions not only from a basic research point of view but also for their potential applications. Since finding the structure-property-processing relationships can open new windows in the application of materials, the material characterizations play a crucial role in the research and development of materials science. The increasing demand for energy with the necessity to find alternative renewable and sustainable energy sources leads to the rapid growth in attention to energy materials. In this book, the results of some outstanding researches on synchrotron-based characterization of nanostructured materials related to energy applications are presented.
English
Keywords: Condensed Matter Physics; Physical Sciences; Engineering and Technology; Material Science; Nanotechnology and Nanomaterials